If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 5x = 7x + 4 Reorder the terms: 6 + 5x = 4 + 7x Solving 6 + 5x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 5x + -7x = 4 + 7x + -7x Combine like terms: 5x + -7x = -2x 6 + -2x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -2x = 4 + 0 6 + -2x = 4 Add '-6' to each side of the equation. 6 + -6 + -2x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 4 + -6 -2x = 4 + -6 Combine like terms: 4 + -6 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| 21+5x=8x+12 | | 14+14x=21+7x | | 16+11x=20+7x | | 2m^2-4m+1=0 | | 60+2x=12x+50 | | 7+13x=6x+42 | | 8+10x=2x+32 | | 4x+13=12+9x | | 54+15x=72+6x | | 5x+63=12x+35 | | 10x+14=3x+42 | | 5x+90=15x+40 | | 6x+32=24+10x | | 36+14x=63+5x | | 12+10x=18+7x | | 6x+24=9x+6 | | 36+14x=72+5x | | 12+8x=4x+36 | | 8x+42=14x+36 | | 6x+28=16+10x | | 8+7x=10+5x | | 5x+42=12x+14 | | 3x+7+2(3+x)= | | 4x+10=2+6x | | 24+7x=12+10x | | 2x+30=10+7 | | 42+4x=10x+24 | | 3x+7+3(3+x)= | | 20+15x=70+5x | | 66+12x=1x+88 | | 6x+64=14x+48 | | 7x+40=10+12x |